Peran Pajak Parkir dalam Menunjang Pendapatan Asli Daerah (PAD) di Kota Probolinggo - Achmad Fauzi Imron (Fakultas Ekonomi dan Bisnis Islam, 2016)
With a wide range of problems arising out of the parking tax in Kota Probolinggo such as illegal parking, parking attendants who do not follow the rules, the parking tax could still meet its target and could still play a role in supporting the regional revenue in Kota Probolinggo. Departing from that background the writer wants to discuss the thesis with the title “The Role of Taxes Parking In Supporting Local Revenue In Kota Probolinggo”. The focus of the problem in this research is how the role of the parking tax in the region income support, Probolinggo, how to support the construction of the parking tax in Kota Probolinggo. The study, the researchers used a qualitative approach. The author uses the method of observation, documentation and interview. As for the analysis of data the author uses descriptive analysis is the data analysis done by way of describing the data with the data logical reasoning to reflect the condition of the object of research. Results can be delivered by the author that role in supporting the parking tax revenue Probolinggo city can be seen from the targets are always met even always exceeded, and the target that year after year is increasing. The existence of a parking tax collection in addition to supporting the PAD, can also indirectly have a positive impact both on the government and the City of Probolinggo Probolinggo City community such, can provide / hiring people in Probolinggo.